Regional risk-sharing in Ukraine - Jarko Fidrmuc; Serhiy Moroz; Fabian Reck (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
This paper analyzes the impact of ethnic heterogeneity and military conflict on the degree of regional consumption risk-sharing in Ukraine. Ethnicity and violent conflicts can influence risk-sharing e.g. through social capital, ethnic fractionalization, migration, and remittances. The sample consists of 25 Ukrainian oblasts and covers the highly volatile period from 2003 to 2016. Our results suggest that the degree of consumption risk-sharing is comparably high; between 70 and 80 percent on average. Moreover, consumption risk-sharing is significantly higher in the regions with a large Russian minority, which are enjoying special treatment by Russia. By contrast, the degree of financial development, as proxied by deposit and loan share in GRP, does not significantly affect the regional degree of consumption risk-sharing. Furthermore, we apply spatial models to control for spatial dependence across regions. Results are confirmed and it is shown that spatial correlation is important. Finally, we show that the recent geopolitical conflict in east Ukraine changed the regional degree of consumption risk-sharing.
URN:NBN:fi:bof-202011232500
Keywords: E32; E21; R12; P25; 330; Ukraine; risk-sharing; ethnic heterogeneity; social capital; remittances; spatial regression